Amazon Adventure Ratonian finds intrigue in rainforest - Wildermuth, Todd (Raton, New Mexico Raton Range, 1997)
Newspaper Article on Denise Bacca and her training to become an Amazon rainforest "trip leader" and her travels there.
Master list item #:47
File location is in the Raton File Cabinet
Keywords: Bacca, Denise; Smith, Morgan; Bacca, Ken; Local History; Biography; Life and Customs; Rainforest; Tribal People; Environmental education; Tourist; Rainforest -- Oxygen -- Education; Raton, New Mexico; Peru; Alabama; Iquitos, Peru